2010
DOI: 10.1073/pnas.1000759107
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella pathogenicity island 2 expression negatively controlled by EIIA Ntr –SsrB interaction is required for Salmonella virulence

Abstract: SsrA/SsrB is a primary two-component system that mediates the survival and replication of Salmonella within host cells. When activated, the SsrB response regulator directly promotes the transcription of multiple genes within Salmonella pathogenicity island 2 (SPI-2). As expression of the SsrB protein is promoted by several transcription factors, including SsrB itself, the expression of SPI-2 genes can increase to undesirable levels under activating conditions. Here, we report that Salmonella can avoid the hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
72
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(81 citation statements)
references
References 41 publications
7
72
0
2
Order By: Relevance
“…Second, deletion of EIIA Ntr was found to indirectly affect the virulence of this pathogen. EIIA Ntr was reported to interact with the response regulator SsrB, which is required for the expression of numerous genes located within pathogenicity island 2 of this bacterium (131). The interaction with EIIA Ntr prevents SsrB from stimulating the expression of the genes in pathogenicity island 2.…”
Section: Fig 5 Pts-catalyzed Glucose Uptake and The Eiiamentioning
confidence: 99%
“…Second, deletion of EIIA Ntr was found to indirectly affect the virulence of this pathogen. EIIA Ntr was reported to interact with the response regulator SsrB, which is required for the expression of numerous genes located within pathogenicity island 2 of this bacterium (131). The interaction with EIIA Ntr prevents SsrB from stimulating the expression of the genes in pathogenicity island 2.…”
Section: Fig 5 Pts-catalyzed Glucose Uptake and The Eiiamentioning
confidence: 99%
“…Third, EIIA Ntr has also been shown to be a member of the E regulon and to play a role in maintaining cell envelope integrity upon stress (444). Fourth, for Salmonella, EIIA Ntr has been demonstrated to interact directly with SsrB, the response regulator of the SsrA/SsrB two-component system that mediates survival and replication within host cells (445).…”
Section: Figmentioning
confidence: 99%
“…17 Plant and animal pathogens can be disseminated into the environment, which can potentially have an important influence on pathogen evolution (see also Morris et al). 109 For example, pathogens may be exposed to a variety of bacteriophages [e.g., vibriophages], 52 and they frequently encounter other organisms that may act as alternative hosts and have resident microbial populations. 110 Moreover, several virulence genes in human pathogens have been experimentally determined to provide resistance to grazing protozoa 111,112 or to kill amoeba associated with them in biofilms.…”
Section: Alternative Hosts and Environments As Mge Reservoirs For Dnamentioning
confidence: 99%
“…It was found that this PAI has integrated into the host regulatory network and is expressed only at the critical times of infection, but switched off at other times to avoid toxicity or energy burdens. 52 Investigations into GIs are helping to unravel host range restriction in a number of pathogens. Salmonella enterica Gallinarum is a pathogen with a host range specific to poultry, while S. enterica Enteritidis is a broad host range pathogen that is a leading cause of gastrointestinal salmonellosis in humans and many other species, but only colonizes poultry sub-clinically (i.e., is asymptomatic).…”
mentioning
confidence: 99%